Language Means of Revealing Postmodern Ludic Absurd in English Literary Text - Babelyuk, Oksana; Koliasa, Olena; Smaglii, Valeriia (Տիգրան Մեծ)
The fiction politics of contemporaneity reflects diversified patterns of language forms and their functions. This has brought to life experimental (postmodernist) writing the key principles of intertextuality, fragmentation, destruction, play. Postmodernist aesthetics caused a blurring of traditional genre canons that led to contamination of syncretic genre compounds through a grotesque transformation of traditional genre models and created an „estrangement‟ effect. The phenomenon of ludic absurd is viewed in three aspects: 1) linguo-philosophical; 2) cognitive; 3) poetic. The present study focuses on the analysis of ludic absurd; the role of graphic, phonetic, morphemic, wordforming, syntactical, semantic mechanisms, based on the intentional deviation of language norm, play on words; cognitive mechanisms, generated by ad-hoc way of thinking. The conducted linguopoetic analysis of American postmodern short stories suggests that ludic absurd as a stylistic device of postmodern poetics manifests itself at all language levels (lexical, syntactic, semasiological, and textual) and is realized via the semantic asymmetry of lexical units, using illogical, but grammatically correct syntactic constructions, syntactic mismatch of sentences and whole text fragments. Prospects for further studies consist in clarifying the pragmatic role of ludic absurd in the postmodern literary text; expanding the taxonomy of lexicosemantic, stylistic, and syntactic and paragraphemic means of ludic absurd.
Keywords: Philosophy; Language